(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2022)
The politics of disgust weaponizes the bodily recoil of revulsion to legitimate sexist, anti-Semitic, colonial and genocidal violence. Citing the work of neurologists, psychologists, existentialists and phenomenologists, I argue that disgust can be severed from this politics to serve a politics of the body where the repugnance of disgust is reserved for those who repudiate the humanity of our intersubjective vulnerability.